Review of the experience with monitoring uncertainty requirements in the Clean Development Mechanism. (17th August 2016) - Shishlov, Igor; Bellassen, Valentin
Abstract : In order to ensure the environmental integrity of carbon offset projects, emission reductions certified under the Clean Development Mechanism (CDM) have to be 'real, measurable and additional', which is ensured, inter alia, through the monitoring, reporting and verification (MRV) process. MRV, however, comes at a cost that ranges from several cents to €1.20 and above per tCO2 e depending on the project type. This article analyses monitoring uncertainty requirements for carbon offset projects with a particular focus on the trade-off between monitoring stringency and cost. To this end, existing literature is reviewed, overarching monitoring guidelines, as well as the ten most-used methodologies are scrutinized, and finally three case studies are analysed. It is shown that there is indeed a trade-off between the stringency and the cost of monitoring, which if not addressed properly may become a major barrier for the implementation of offset projects in some sectors. It is then demonstrated that this trade-off has not been systematically addressed in the overarching CDM guidelines and that there are only limited incentives to reduce monitoring uncertainty. Some methodologies and calculation tools as well as some other offset standards, however, do incorporate provisions for a trade-off between monitoring costs and stringency. These provisions may take the form of discounting emissions reductions based on the level of monitoring uncertainty – or more implicitly through allowing a project developer to choose between monitoring a given parameter and using a conservative default value. Policy relevance The CDM Executive Board acknowledged that monitoring uncertainty has not been treated in a consistent manner and the draft standard on uncertainty was subsequently presented in May 2013. This article supports the implementation of this standard for more comprehensive, yet cost-efficient accounting for monitoring uncertainty in carbon offset projects. Moreover, in the light of the ongoing discussions on the New Market Mechanisms as well as the operationalization of the Green Climate Fund and different national mitigation policies, the CDM experience provides valuable insights with regards to the treatment of monitoring uncertainty and constitutes a solid basis for designing uncertainty requirements for new mechanisms to mitigate climate change.